Espesor de la filtración adicional de aluminio en radiología odontológica: 1,5 ó 2.0 mm de al? - Aranha-Watanabe, Plauto Christopher; Pardini, Luis Carlos; Tamburus, Jose Roberto (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The purpose of this study was to compare radiation dose, radiographic quality, density and contrast of radiographic films group D(fitraspeed-Eastman Kodak Co.), radiografied with additional filtration of Aluminum 1.5 and 2.0 rrun., with and without simulating banier of soft- material. Four groups were analized, each one with five films in a predetermined path and geometric factor. Exposure time was 1 second and the distance from the film was 40 cm. After manual film processing fotodensitornetric lectures were realized and data was presented. Iliperbolic transformation of original data was verified and the values of "a" (density) and "b" (contrast), were reached by the liner regression of transformed data. Our results demonstrated a reduction of 24% radiation dose when an additional filtration 012.0 rnm. were used over 1.5 mm. filtration. Statistical test presented significant differences (P<0.05) for radiographic density and no differences for radiographic contrast. We concluded that a 2.0 .mm Aluminum filtration is recommended for an X Rays machine operating with 65Kvp. Additional filtration for most of the X Rays machines operating in Brasil, must be changed to 2.0 mm considering-ALARA principle.